2015
DOI: 10.1016/j.ijrobp.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fractionation and Dose in a Multivariate Model for Radiation-Induced Chest Wall Pain

Abstract: Purpose To determine the role of patient/tumor characteristics, radiation dose, and fractionation using the linear-quadratic (LQ) model to predict stereotactic body radiation therapy–induced grade ≥2 chest wall pain (CWP2) in a larger series and develop clinically useful constraints for patients treated with different fraction numbers. Methods and Materials A total of 316 lung tumors in 295 patients were treated with stereotactic body radiation therapy in 3 to 5 fractions to 39 to 60 Gy. Absolute dose–absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Likewise, this study found toxicity in the same proportions as previous reports: 31% clinically symptomatic RP [about 10-20% of patients in literature (range: 0-49% among published studies)] with most patients having asymptomatic Grade 1 pneumonitis (2,(15)(16)(17), 14% G1 chest wall pain [10-40% in literature (32)], 7% transient G ≤ 2 radiation dermatitis [12-38% in literature (33)], and 4% rib fractures [0-23% in literature (34)] without other toxicity. No significant predictive factor of chest wall pain, radiation dermatitis or rib fractures was found, probably due to meeting dose constraints (35).…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, this study found toxicity in the same proportions as previous reports: 31% clinically symptomatic RP [about 10-20% of patients in literature (range: 0-49% among published studies)] with most patients having asymptomatic Grade 1 pneumonitis (2,(15)(16)(17), 14% G1 chest wall pain [10-40% in literature (32)], 7% transient G ≤ 2 radiation dermatitis [12-38% in literature (33)], and 4% rib fractures [0-23% in literature (34)] without other toxicity. No significant predictive factor of chest wall pain, radiation dermatitis or rib fractures was found, probably due to meeting dose constraints (35).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies reported that a short distance from the rib and chest wall to the tumor (<1.0–2.0 cm) increases the of risk of RIRFs [ 12 14 ]. However, in the evaluation of risk of RIRF, the use of rib–tumor distance as a risk factor is not appropriate because the dose to the ribs and chest wall can be decreased by use of intensity-modulated radiation therapy (IMRT) techniques, including VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the incidence of RIRF after SBRT for lung tumors was 23–37% [ 9 12 ]. Clinical factors such as target location [ 9 ], female sex [ 10 , 13 ] and rib–tumor distance [ 12 14 ] are known to increase the risk of RIRF and chest wall pain after SBRT for lung tumors. Regarding dosimetric factors, a high-dose-irradiated volume of the chest wall is thought to contribute to the increased the incidence of such adverse events [ 7 , 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 14 An additional chest wall dose constraint was applied on the basis of Memorial Sloan Kettering data evaluating the risk of chest wall toxicity in patients treated with 5-fraction stereotactic body radiation therapy for early stage non-small cell lung cancer. 18 …”
Section: Methodsmentioning
confidence: 99%